Technology and the future of language teaching. (19th February 2018) - Kessler, Greg
Abstract: We are living in a time with unprecedented opportunities to communicate with others in authentic and compelling linguistically and culturally contextualized domains. In fact, language teachers today are faced with so many fascinating options for using technology to enhance language learning that it can be overwhelming. Even for those who are inclined to experiment with emerging technologies, it can be challenging to identify which resources, tools, or Web sites may best fit a particular lesson, activity, or goal. Many of the most compelling opportunities are situated within the same global social and technology trends that have become commonplace in our daily lives, including social media, artificial intelligence, big data, and augmented reality. This article addresses the extent to which technology‐mediated social interactions dominate our daily lives, how we can leverage those interactions to the benefit of our learners, and how we can engage them in learning experiences in ways that will encourage them to practice language extensively. Challenges: Technology offers unprecedented opportunities to communicate with others in authentic and compelling, linguistically and culturally contextualized domains. How can we leverage learners' technologically mediated and highly participatory culture and an array of quickly emerging technologies, including language learning media, artificial intelligence, big data, and augmented reality to enhance language teaching and learning?